Toeplitz Type Operators Associated with Generalized Calderón-Zygmund Operator on Weighted Morrey Spaces. (6th April 2016) - Ren, Bijun; Zhang, Enbin
Abstract : Let T 1 be a generalized Calderón-Zygmund operator or ± I (the identity operator), let T 2 and T 4 be the linear operators, and let T 3 = ± I . Denote the Toeplitz type operator by T b = T 1 M b I α T 2 + T 3 I α M b T 4, where M b f = b f and I α is the fractional integral operator. In this paper, we investigate the boundedness of the operator T b on weighted Morrey space when b belongs to the weighted BMO spaces.